Career prospective: Ask your Alumni / Nor Alwani Omar - Omar, Nor Alwani (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
On May 4, 2019, Persatuan Siswa-Siswi Sains Matematik (PERSIK)had organized a career talk called the Career Prospective: Ask Your Alumni to help the students to identify their self-potential and skills required for future job seeking. A total of 85 students of Diploma in Mathematical Sciences were involved in this programme which was held at UiTM Perak Branch, Tapah Campus. The two alumni invited were Miss Shezrin Hawani Binti Amir Hamzah , a Financial Advisor of Prudential Wealth Planner and Miss Maizatul Akmar Abd Rahman, a banker from Maybank.